2013
DOI: 10.1128/aac.00580-13
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxigenic Clostridium difficile Protects Hamsters against Challenge with Historic and Epidemic Strains of Toxigenic BI/NAP1/027 C. difficile

Abstract: bNontoxigenic Clostridium difficile (NTCD) has been shown to prevent fatal C. difficile infection in the hamster model when hamsters are challenged with standard toxigenic C. difficile strains. The purpose of this study was to determine if NTCD can prevent C. difficile infection in the hamster model when hamsters are challenged with restriction endonuclease analysis group BI C. difficile strains. Groups of 10 hamsters were given oral clindamycin, followed on day 2 by 10 6 CFU of spores of NTCD strain M3 or T7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 23 publications
1
68
0
5
Order By: Relevance
“…Recently, Nagaro et al observed that hamsters infected with nontoxigenic strains were protected from infection with the hyperendemic BI/NAP1/027 strain, which is usually 100% fatal in hamsters (96). Nontoxigenic strains have also been used safely in studies of volunteer patients in prevention of recurrent C. difficile (97).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…Recently, Nagaro et al observed that hamsters infected with nontoxigenic strains were protected from infection with the hyperendemic BI/NAP1/027 strain, which is usually 100% fatal in hamsters (96). Nontoxigenic strains have also been used safely in studies of volunteer patients in prevention of recurrent C. difficile (97).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…Porém, a maioria dos trabalhos sobre modelos animais de ICD são pouco descritivos e deixam em aberto pontos essenciais para reprodução do protocolo de indução, tais como estirpe utilizada, dose de antimicrobiano e forma de administração (BEST et al, 2012). Além disso, a maioria dos estudos relata o uso de amostras de C. diffi cile não disponíveis no Brasil, difi cultando a reprodução em nosso meio (HOWERTON et al, 2013;NAGARO et al, 2013). Dessa forma, o objetivo do presente trabalho foi padronizar um protocolo de infecção por C. diffi cile em hamsters sírios, disponibilizando-o para futuros estudos sobre patogenia, tratamento e métodos de controle da ICD no Brasil.…”
Section: Introductionunclassified
“…Strains that are able to alter bile salt concentrations or limit the availability of other resources may discourage growth of and colonization by C. difficile. Delivery of NTCD is also a promising novel therapy due to its potential competition with toxigenic C. difficile for an intestinal niche (126,127). Future work administering C. scindens and NTCD (128,129) holds promise for the use of these strains as preventative therapies in antibiotic-treated patients or as treatments for CDI.…”
Section: Summary Of Potential Mechanisms Of Action Of Fmt Against CDImentioning
confidence: 99%
“…This strategy is based on observations that people asymptomatically colonized with C. difficile are less likely than uncolonized individuals to develop symptomatic CDI when hospitalized (125). Administration of NTCD following clindamycin treatment in the hamster model protects most animals from death due to challenge with toxigenic C. difficile (126,127). Human studies have also shown some promise for this strategy: phase 1 clinical trials indicated that oral ingestion of NTCD strain VP20621 is safe in healthy humans (128), and phase 2 trials showed that 11% of patients who received VP20621 developed recurrent CDI, in contrast to 30% of patients who received placebo (129).…”
Section: Mechanisms Of Colonization Resistance Against CDImentioning
confidence: 99%